Influence Perception Convenience , Benefit , and Religiosity Regarding the Interest in Using the Gopay E-Wallet among Gen Z in Jepara - Mahmudatus Sadiyah (STIE Amkop Makassar, 2026)
This study aims to analyze the influence of perceived ease, perceived usefulness, and religiosity on the interest in using GoPay e-wallets among Generation Z in Jepara . The study was motivated by the rapid development of financial technology and the increasing use of digital wallets among Gen Z, which is influenced by technological factors and personal values. This study uses a quantitative approach with a survey method by distributing questionnaires to 100 Generation Z respondents in Jepara . The data analysis techniques used include instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing using SPSS software. The results show that perceptions of convenience, perceptions of usefulness, and religiosity have a positive and significant effect on interest in using GoPay e-wallets, both partially and simultaneously. This indicates that the higher the level of ease of use and perceived benefits, and the higher the level of religiosity, the greater the interest of Generation Z in using GoPay . This study is expected to contribute to the development of fintech marketing strategies and serve as a reference for further research related to the adoption of digital financial technology.